Cultural Acculturation in Interior and Architecture of Old Straits-Born Chinese Lasem House - Sri Rachmayanti; Christianto Rusli; Anak Agung Ayu Wulandari (Humaniora, 2017)
The long-term goal of this research was to make variety ornament documentation on architecture and the interior of Indonesian historical buildings, especially for buildings having the combination between western and eastern. The original plan of this research was to achieve some cultural preservation efforts, they were (1) to find various styles of design art, including the variety of native straits-born Chinese ornaments, Art Deco, and Neoclassical, or found that there are any acculturations among the ornaments in an interior. (2) To understand characteristics of each style and applied it appropriately in the interior space. (3) To find on how the building functioned and how to preserve as cultural heritage. The method began with a survey, interviews, and observations by documenting the application of Indonesia art and culture for cultural conservation, especially on interior design. The case study was straits-born Chinese buildings in Lasem, Central Java. The observation and research concerned with design styles applied in architecture, interior, and home decoration. The observation and research were followed by summarizing and analyzing the material obtained from field surveys result by comparing two samples of Chinese houses in Lasem that also supported with literature research. Researchers find several differences of art styles which had been applied. The styles are original Chinese decorations, Art Deco, and Neoclassical decorations.